Overview of the Mixed Script Information Retrieval (MSIR) - banerjee, Somnath; Chakma, Kunal; Naskar, Sudip Kumar; Das, Amitava; Rosso, Paolo; Bandyopadhyay, Sivaji; Choudhury, Monojit (Proceedings of FIRE 2016, 2016)
The shared task onMixed Script Information Retrieval (MSIR) was organized for the fourth year in FIRE-2016. The track had two subtasks. Subtask-1 was on question classification where questions were in code mixed Bengali-English and Bengali was written in transliterated Roman script. Subtask-2 was on ad-hoc retrieval of Hindi lm song lyrics, movie reviews and astrology documents, where both the queries and documents were in Hindi either written in Devanagari script or in Roman transliterated form. A total of 33 runs were submitted by 9 participating teams, of which 20 runs were for subtask-1 by 7 teams and 13 runs for subtask-2 by 7 teams. The overview presents a comprehensive report of the subtasks, datasets and performances of the submitted runs.